Regulations Regarding Nonfinancial Reporting and Socially Responsible Behavior - Mihai-Florentin Herciu (Ovidius University Annals: Economic Sciences Series, 2021)
The socially responsible behaviour of economic entities and non-financial reporting are subjects of maximum interest in the business environment, given that they have had a major impact on the way economic activities are conducted, from the perspective of stakeholders. They are interested in the impact of the companies on the society as a whole, wishing to be informed about non-financial issues in addition to those of a financial nature. The purpose of this paper is to highlight certain regulations and norms that were meant to implement in corporate conduct the socially responsible behavior or that provided directions to be followed in terms of non-financial reporting. In this respect, an evolutionary analysis of the main regulations was carried out, highlighting defining aspects for each of them, independently and comparatively. The results of the research have highlighted the existence of many regulations concerning non-financial reporting, each with a different audience, with the desire to harmonise the regulations concerning non-financial reporting being highlighted.